The Study and Evaluation of ARM-Based Mobile Virtualization. (7th July 2015) - Xu, Lei; Wang, Zonghui; Chen, Wenzhi
In common sense, virtualization technology is adopted to offer several isolated execution environments and make better use of computational resources in server environment. However, in embedded systems, the significance of virtualization does not come into the picture. The extensive utilization of mobile smart devices has led to a series of issues such as security, wasting of resources, and power consumption. In this paper, we discuss how mobile virtualization addresses these challenges and then present a detail analysis of four mainstream mobile virtualization solutions: containers, paravirtualization, hardware-assisted full virtualization, and microkernel. At last, we carry out a series of performance comparisons among these solutions and make some suggestions for further research.